2004
DOI: 10.1080/1016873042000299981
|View full text |Cite
|
Sign up to set email alerts
|

Financial development and economic growth in Greece: an empirical investigation with Granger causality analysis

Abstract: This paper empirically examines the causal relationship between the degree of openness of the economy, financial development and economic growth by using a multivariate autoregressive VAR model in Greece for the examined period 1960:I-2000:IV. The results of cointegration analysis suggest that there is one cointegrated vector among GDP, financial development and the degree of openness of the economy. Granger causality tests based on error correction models show that there is a causal relationship between finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 35 publications
8
69
0
5
Order By: Relevance
“…Standard deviation of many economic time series is approximately proportion to its level and standard deviation of the logarithm of the series is approximately constant. In either case it was useful to transform the series so that changes in the transformed series are proportional changes in original series { (Stock and Watson, 2004), (Loayza and Ranciere, 2006), (Chang, 2002), (Dritsakis, 2004)}.…”
Section: Model Specificationmentioning
confidence: 99%
“…Standard deviation of many economic time series is approximately proportion to its level and standard deviation of the logarithm of the series is approximately constant. In either case it was useful to transform the series so that changes in the transformed series are proportional changes in original series { (Stock and Watson, 2004), (Loayza and Ranciere, 2006), (Chang, 2002), (Dritsakis, 2004)}.…”
Section: Model Specificationmentioning
confidence: 99%
“…Also, exports leads to investment, investment stimulates further investment and finally leads to growth (Jha, 2006). Past researches had ascertained cointegrating relationships between growth, investment and exports for Japan (Amano, 2005), Greece (Dritsakis et al, 2006), Romania (Marinas, 2007), Vietnam (Anh, 2008), korea and Taiwan (Yoo, 2008), Turkey (Akhtar et al, 2008), Nigeria ( Chimobi, 2010), China (Herrerias and Ortis, 2010), and Malaysia (Tan and Lean, 2010). These studies have had used cointegration to study the impact of export and domestic investment on the GDP.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, Levine (1997), Liang and Teng (2006), Ang and McKibbin (2007), Panopoulou (2009), Odhiambo (2010, Kar et al (2011) and Pradhan and Gunashekar (2013) have found evidence in favour of the hypothesis of growth-led financial development (in other words, the demand-following hypothesis). Yet other studies such as those by Ahmed and Ansari (1998), Craigwell et al (2001), Calderon and Liu (2003), Dritsakis and Adamopoulos (2004), Darrat et al (2006), Wold-Rufael (2009) and Yucel (2009) support the validity of bidirectional causality between the two, where causality proceeds in both the directions (in other words, the feedback hypothesis). It should be noted that Robinson (1952) and Lucas (1988) maintain that there is no causal relationship between the two variables (in other words, they adopt the neutrality hypothesis).…”
Section: Review Of Three Sets Of Literaturementioning
confidence: 92%